Analisis Yuridis Penyelesaian Sengketa Bisnis Melalui Konstruksi Hukum Tanggung Renteng: Studi Putusan No. 833/Pdt.G/2024/PN Jkt.Utr - Pangeran M S Sitorus (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2026)
The development of the modern business world is marked by the increasing complexity of legal relationships between business actors, involving various entities with close economic and operational interconnections. This condition creates challenges in civil dispute resolution, especially when default occurs in multi-party business agreements. This study aims to analyze the application of the joint and several liability (tangung renteng) legal construction as a business dispute resolution mechanism in the Decision of the North Jakarta District Court Number 833/Pdt.G/2024/PN Jkt.Urr. This research uses normative legal research methods with statutory, conceptual, and case approaches. The legal materials used consist of primary legal materials in the form of legislation and court decisions, as well as secondary legal materials in the form of legal books and journals, which are analyzed descriptively-analytically. The results show that the panel of judges applied the joint and several liability construction not only based on formal contractual relationships, but also on the factual and economic interconnections between the parties, such as the receipt of benefits, operational integration, and the commingling of assets between the business entity and its management. The application of this construction proves effective in expanding the basis of liability and guaranteeing the recovery of creditor's rights. However, the decision also shows limitations in proving commercial immaterial losses, which are still bound by strict civil evidence standards. This study concludes that the joint and several liability construction can be an important instrument in resolving multi-party business disputes, but clearer jurisprudential guidelines are needed to ensure legal certainty and consistency of its application in the future.